Relationship between Halal Traceability System Adoptions on Halal Food Supply Chain Integrity and Performance - Ab Rashid, Norasekin; Supian, Kamisah; Bojei, Jamil (International Journal of Asian Social Science, 2018)
The increase number of cases on the misused of Halal logo and questionable status of Halal food indicate that there are weaknesses in the procedure of determining Halal food. In this case, food companies must be prepared to implement traceability system to ensure the authenticity of Halal products. Accordingly, the main purpose of this study is to examine the relationship between the Halal traceability system adoption on Halal food supply chain integrity and performance. Using a quantitative research approach, survey questionnaires were distributed to 127 Malaysian Halal food and beverages companies during Halal exhibitions. Partial Least Squares (PLS) software was applied to examine the direct effect hypotheses. The results revealed that Halal traceability system adoptions were significantly importance in enhancing Halal food supply chain integrity and performance. The study has successfully filled the gap in literature by empirically establishing the relationship between Halal traceability system adoption on Halal food supply chain integrity and performance.